The Deliberative Referendum: An Idea Whose Time has Come?. Issue 3 (March 2023) - Hendriks, Frank; Wagenaar, Charlotte
While deliberative citizens' assemblies and plebiscitary referendums have long been perceived as antithetical, the idea of combining the two democratic instruments for better connecting administration and society has come to the fore in both theory and practice in more recent years. In this article, three ways of linking citizens' assemblies to the referendum process are distinguished, exemplified, institutionally compared, and reflectively discussed. The three—the referendum-preparing, referendum-scrutinizing, and referendum-elaborating citizens' assembly—come with their distinctive features, potential merits, scope limits, and related design questions. Fitting the "square peg of deliberative democracy" into the "round hole of direct democracy" and embedding hybrid design in diverging political systems are overarching challenges of institutional design. The article concludes that considering recent developments in theory and practice, the idea of a deliberative referendum linking citizens' assemblies to direct voting on issues, seems an idea whose time has come, but also comes with challenges and questions that design thinkers and practitioners have only begun to tackle and answer.